Radiocarbon dates (Scottish Historical and Archaeological Internet Reports, 2012)
A total of eighteen dates were obtained and there are problems with the results. Two dates from burnt bone can be discounted as unreliable, however, the remaining sixteen show a significant lack of cohesion even within individual contexts. Possible reasons for this are considered.